2008
DOI: 10.1111/j.1365-2591.2008.01384.x
|View full text |Cite
|
Sign up to set email alerts
|

Radicular peroxide penetration from carbamide peroxide gels during intracoronal bleaching

Abstract: Peroxide penetration of CP gels was significantly lower than that of a HP-SP mixture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 26 publications
2
26
0
2
Order By: Relevance
“…Its effectiveness depends mainly on the chemical oxidation process (22); however, the oxidizing agents can reduce the adhesion of the resin materials to the dentin (1). Gökay et al reported the radicular peroxide penetration from CP during an intracoronal bleaching procedure (18). The results showed that the root dentin's peroxide penetration may reduce the bonding strength of the fiber posts to the canal walls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its effectiveness depends mainly on the chemical oxidation process (22); however, the oxidizing agents can reduce the adhesion of the resin materials to the dentin (1). Gökay et al reported the radicular peroxide penetration from CP during an intracoronal bleaching procedure (18). The results showed that the root dentin's peroxide penetration may reduce the bonding strength of the fiber posts to the canal walls.…”
Section: Discussionmentioning
confidence: 99%
“…It can be argued that the oxygen radicals might penetrate deeper into the root regions when the lower bonding strengths of the fiber posts cemented immediately after the bleaching process are taken into account. In the literature, it has been shown that the oxygen radicals can penetrate into the dentin tubules (18). Additionally, one previous study reported that the glass-ionomer cement, which acts as a barrier, may not prevent the leakage of the bleaching agent (19).…”
Section: Idr -Volume 8 Number 1 2018mentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogen peroxide that is the main component of all bleaching agents, can diffuse through dentin and cementum and reaches periodontal tissues [5,19,20], causing damage effects from mild inflammation to external cervical root resorption [6].…”
Section: Discussionmentioning
confidence: 99%
“…Tooth permeability to bleaching agents occurs due to its low molecular weight and the ability of denature proteins, allowing the penetration of hydrogen peroxide to the pulp chamber and periodontal tissue [4,5]. Several authors reported that bleaching agents can penetrate in the dentinal tubules and initiated an inflammatory process which might promote a cervical external root resorption [6] after non-vital dental bleaching in teeth with or without defects in the cementumenamel junction [7,8].…”
Section: Cytotoxicity Testingmentioning
confidence: 99%